Knowledge Of Colorectal Cancer Among Patients Presenting With Rectal Bleeding And Its Association With Delay In Seeking Medical Advice - Syahnaz Mohd Hashim; Tong Seng Fah; Khairani Omar; Shamsul Azhar Shah; Ismail Sagap; Mohd Radzniwan A Rashid (Asian Pacific Organization for Cancer Prevention, 2024)
Indexed by Scopus